Water in Road Structures Movement, Drainage & Effects - Dawson, Andrew (Geotechnical, Geological and Earthquake Engineering,, 2009)
Water in and beneath a road pavement has a major impact on the road's performance and its survivability. This book provides a state-of-the-art on the topic of water in pavements and the adjacent ground. It includes coverage of the basic theory; where the water comes from; how it may (or may not) be drained; the effect of temperature on the movement; how movements may be modelled numerically; and the impact that water content has on pavement material and subgrade behaviour. Sections on instrumentation and monitoring are also provided. With increased concerns that road construction may introduce contaminants into the environment, the book also studies environmental aspects of water in roads and their immediate surroundings by describing the leaching action of pavement water; the opportunities for the pavement to sorb contaminants from pavement run-off; water sampling; and water quality needs. It draws on information from a wide variety of sources, particularly in Europe and the USA, both published and unpublished, having been written by a broad team of practising engineers, hydrogeologists, environmental scientists and researchers. This book is the principal output of a large collaborative study performed as part of the COST programme, managed by the European Science Foundation. .